Unexplored Energy Storage Potential in Household Appliances for Electric Grid Stabilization - Breskvar, Uroš (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Current strategies for energy storage in energy systems primarily rely on battery technologies. However, there is significant untapped potential for energy storage in the form of heat or cold, which can be provided by household appliances such as refrigerators, freezers, and water heaters. In this study, we examined how adjusting the operation of these devices contributes to stabilizing the electricity grid and supports the integration of intermittent renewable energy sources. We present an analysis of the technical capabilities and energy potential of these devices, as well as their impact on the efficiency and sustainability of the grid's operation. The results of the study indicate that optimal management of these devices can reduce grid loads and enhance its flexibility, which is crucial for the future of sustainable energy systems.